Diversity of eating patterns and obesity in older adults: a new challenge - Ferreira, Patricia Moraes [UNESP]; Papini, Sílvia Justina [UNESP]; Corrente, José Eduardo [UNESP] (Scientific Research Publishing, 2013)
The increase in the variety of food choices influences the eating patterns of older adults, which is in turn increases the occurrence of obesity. This study aimed at identifying eating patterns and their association with obesity in a representative sample of older adults living in an urban area and registered in the basic health unit in the city of Botucatu, São Paulo, Brazil. This is a cross-sectional study and data collection took place from March to June of 2011 through the application of a validated food frequency questionnaire for older adults, a sociodemographic survey and an anthropometric evaluation. Eating patterns were identified through principal component analysis. Scores of individual consumption were divided in tertiles, characterizing as low, moderate or high adherence of the individuals to each pattern. Logistic regression models were fitted for the outcomes “general obesity” and “abdominal obesity” and the tertiles of consumption adjusting by sociodemographic variables. Six eating patterns were identified: Healthy foods, Snacks and weekend meals, Fruits, Light and whole foods, Mild diet and Traditional diet. It was found that the adherence to healthy foods is protective against obesity as well as adherence of snacks and weekend meals are risk of obesity. Eating patterns and their recognized influence on obesity comprise an issue that deserves continuous attention in order to evaluate collectively the eating profile, and develop specific nutritional guidelines for older adults.
Keywords: Eating patterns; General obesity